2008
DOI: 10.2174/187221208784705233
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Patents in Tyre Cooling

Abstract: Recent Patents On Engineering 2 (2008) pp. 87-94Netscher et al. 2 ABSTRACTA number of patents on tyre cooling have been reviewed with a focus on those which can be applied to earthmoving tyres for the mining industry. The mechanisms of heat transfer within the tyre carcass are introduced as well as the basic tyre structure and effects of overheating on tyre operation. The tyre cooling patents are separated into five functional groups and reviews are made based on practicality and potential for significant heat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…This is due to the reduction in the internal damping in the rubber, and consequently strong increase in the crack tip propagation velocity (see, e.g., figure 5). This effect is well documented experimentally, e.g., studies by S A Bridgestone (2002), reported on in [29], show a decrease in the tire life for truck tires by a factor of ∼5 as the environmental temperature increases from 5 to 40 • C.…”
Section: Rubber Wear Ratesupporting
confidence: 62%
“…This is due to the reduction in the internal damping in the rubber, and consequently strong increase in the crack tip propagation velocity (see, e.g., figure 5). This effect is well documented experimentally, e.g., studies by S A Bridgestone (2002), reported on in [29], show a decrease in the tire life for truck tires by a factor of ∼5 as the environmental temperature increases from 5 to 40 • C.…”
Section: Rubber Wear Ratesupporting
confidence: 62%
“…A tire consists of bead-in contact with the rim of the wheel, carcass-the framework of the tire, and tread-the focus of this study-is in direct contact with the road and therefore, exposed to extensive abrasion [28] (Figure 1). The rotation of the tire under the weight of the vehicle results in repeated deformation that generates high friction and consequent elevation in its temperatures [29], e.g., 120 °C was measured in tires of trucks [30]. Therefore, high TC [31] of the tread is essential to efficiently dissipate the heat (vide infra).…”
Section: The Rubber Matrixmentioning
confidence: 99%
“…These properties are interlinked; friction energy is directly converted into heat, resulting in temperature elevation of the tire. The poor thermal conductivity of the tread compound loaded with CB (0.27 W m −1 K −1 ) [30] results in a higher rate of heat generation than The rotation of the tire under the weight of the vehicle results in repeated deformation that generates high friction and consequent elevation in its temperatures [29], e.g., 120 • C was measured in tires of trucks [30]. Therefore, high TC [31] of the tread is essential to efficiently dissipate the heat (vide infra).…”
Section: The Rubber Matrixmentioning
confidence: 99%
See 1 more Smart Citation